The Level of Fisherman's Welfare in Tapian Nauli I Village Tapian Nauli Subdistrict Tapanuli Tengah Regency - Vio Ericha Siahaan; Kusai Kusai; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in June 2017 in Tapian Nauli I Village, Tapian Nauli Subdistrict, Tapanuli Tengah Regency, North Sumatera Province. The purpose of this study to determine the social and economic characteristics of fisherman households, and the level of welfare of household fisherman owners and fisherman laborers in the Village Tapian Nauli I. The method used in this research is a survey method. Retrieval of respondents using proportionate stratified random sampling. The technical analysis used are descriptiveanalysis and bogardus analysis. The result showed that social and economic characteristics of the fisherman is the age of fisherman as much as 72% classified as very productive.Educational level of the average fisherman still belongs to low. The number of dependent families of fishermen as much as 56% belongs to the medium. The fisherman’s family has two income there were fixed income from fishing, and income from several their wives. The income of fisherman is moderate. The level of fisherman ownerswelfare based on BKKBN (Badan Koordinasi Keluarga Berencana Nasional) is as much as 80% are on welfare level phase I, while 90% of fisherman laborers areat the level of welfare phase I. Keywords: prosperity, fisherman, bkkbn, Tapian Nauli I Village.